The return to investment on education in the banking sector / Farrah Dina Abd Razak, Jamilah Laidin and Ainun Mardiah Mohd Hanifah - Abd Razak, Farrah Dina; Laidin, Jamilah; Mohd Hanifah, Ainun Mardiah (2012)
This article examines the return from investment in education and how it links with agendas for sustainable development. Concept of sustainable development in economics studies can be referred as a 'path of rising per capita well being'. Rising in per capita can be achieved through accumulation of human capital. Human capital is the major contributor in driving a nation's economic growth. It refers to education, training, experience and health personified in workers which can increase their productivity. Do economy can succeed without a highly skilled population that is able to respond quickly and creatively to economic fluctuations. Education and training are key for moving society toward sustainability. Investment in education is one of the ways to increase human capital in a country and it can be measured through the increase in income received. This study evaluates the returns to investment on education by using Mincerian earnings function and examines some of the factors that affect earnings. Data were collected from a survey in the banking sector in 2010.